Queen of babble - Cabot, Meg (Avon, 2007)
Lizzie Nichols discovers that her inability to keep her mouth shut has landed her in hot water when she aggravates her unfaithful boyfriend, is stranded in London, and takes a job as a bartender for a catered wedding at a French château.